Proposta de uma nova técnica para extração global de máxima potência de módulos fotovoltaicos sem sensoriamento da corrente e da tensão provenientes da fileira fotovoltaica - Pires, Lucas Pereira (2019)
The technological advance of the last decades has culminated in the expansion of grid-tied photovoltaic systems in Brazil and abroad, bringing with it the interest of the scientific community in the search for Global Maximum Power Point Tracking (GMPPT) techniques that are efficient, simple and cheap. In this context, the present work proposes a new GMPPT strategy that uses only the voltage and current sensors at the point of connection to the grid, reducing the costs of power inverters. To reach the maximum power point (MPP) a disturbance is performed on a variable called Tolerance, which in turn constitutes the maximum permissible error value between the reference current and the current imposed on the output inductor (DeltaRMS). The peak current used as a reference in the inverter control is incremented or decremented according to the comparison between Tolerance and DeltaRMS. The entire design of the proposed technique and its controllers is described in detail. In order to perform performance comparison, the classic MPPT techniques Perturb and Observe and Incremental Conductance are also included in all stages of the work. The experimental results presented a high tracking factor (TF) for the proposed technique (99.90%), and also had an excellent response regarding the identification of false maximum power points from the scanning of the characteristic curve with the subsequent targeting of the operation to the global maximum power point.